Observation of a mesoscale warm eddy impacts acoustic propagation in the slope of the South China Sea - Chen, Wen; Zhang, Yongchui; Liu, Yuyao; Wu, Yanqun; Zhang, Yun; Ren, Kaijun (Frontiers in Marine Science, 2022)
Acoustic rays are modified while propagating through oceanic eddies. However, due to the lack of field synchronous observation, the impact of mesoscale eddy on the acoustic propagation is less clarified. To address the issue, an eddy-acoustic synchronous observation (EASO) field experiment for a mesoscale warm eddy was carried out in the slope of the South China Sea (SCS) in October, 2021. During the field experiment, a total of 105 conductivity-temperature-depth (CTD) stations, as well as a zonal acoustic survey line through the center of the warm eddy, were obtained. The vertical structures of temperature and salinity indicate that the warm eddy is surface-intensified with temperature and salinity cores confined within depths from 70 m to 200 m and 10 m to 70 m, respectively. The acoustic observation shows two obvious convergency zones (CZs) at about 39 km and 92 km in the eastern half acoustic line, and one convergency zones (CZ) at about 25 km in the western half acoustic line. By comparing with the none eddy circumstance, the respective impacts of the topography and warm eddy are quantitatively analyzed with a ray-tracing model. The results indicate that the topography shortens the horizontal span of the CZ by 11.4 km, while the warm eddy lengthens it by 1.7 km. Additionally, the warm eddy shallows the depth and broadens the width of the CZ by 32 m and 1.4 km, respectively. The anisotropy of 3D sound fields jointly influenced by the warm eddy and the local topography show that the distance differences of the first CZs in different horizontal directions can be as long as 31 km.